THE EFFECTIVENESS OF THE DOCUMENTARY FILM MEDIA "SHUT UP AND LISTEN" AGAINST ECOLITERACY OF STUDENTS IN SOCIAL SCIENCES LEARNING - Agniya Tazkiya; Eldi Mulyana; Lili Dianah (Journal Civics And Social Studies, 2023)
Humans in fulfilling their needs make use of available natural resources, but the impact of this human activity can affect the environment, namely the emergence of environmental problems. To reduce environmental problems, awareness of the importance of protecting and preserving the environment is needed. This can be done one of them through education, especially for students. This study aims to test and see the effectiveness of the use of the documentary film "Silence and Listen" to the ecoliteracy of class VII students at SMPN 5 Garut. This research method uses a quasi-experimental method with a nonequivalent pretest posttest control group design. The sample in this study were students of class VII-H as the experimental class and class VII-F as the control class. The instruments used in this study were tests and observations. After collecting data, then the data is processed using SPSS v29 software. This study concluded that there were differences in the ecoliteracy of students before and after treatment using the documentary film "Silence and Listen". This ecoliteracy difference is based on a hypothesis test which shows a value (Sig 2-tailed) 0.046 <0.05 meaning that Ha is accepted and Ho is rejected. So that the documentary film media "Silence and Listen" is effective in increasing the ecoliteracy of class VII students at SMPN 5 Garut.